2022
DOI: 10.3390/brainsci12101355
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Tau Burden Is Associated with Abnormal Brain Functional Connectivity in Alzheimer’s Disease: A 18F-Florzolotau Study

Abstract: Purpose: 18F-Florzolotau is a novel second-generation tau radiotracer that shows higher binding affinity and selectivity and no off-target binding. The proportion loss of functional connectivity strength (PLFCS) is a new indicator for representing brain functional connectivity (FC) alteration. This study aims to estimate the relationship between the regional tau accumulation and brain FC abnormality in Alzheimer’s disease (AD) and mild cognitive impairment (MCI) patients based on Florzolotau PET and fMRI. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…The aim was to confirm that all potential participants were devoid of any indicators of intracranial hemosiderin/ferritin, brain tumors, cerebrovascular lesions, or calcification. rs-fMRI images were preprocessed in accordance with the previously reported steps 27 (Data Processing Assistant for Resting-State fMRI ( http://www.rfmri.org/DPARSF )), spatially normalized, and smoothed. 12 , 15 …”
Section: Methodsmentioning
confidence: 99%
“…The aim was to confirm that all potential participants were devoid of any indicators of intracranial hemosiderin/ferritin, brain tumors, cerebrovascular lesions, or calcification. rs-fMRI images were preprocessed in accordance with the previously reported steps 27 (Data Processing Assistant for Resting-State fMRI ( http://www.rfmri.org/DPARSF )), spatially normalized, and smoothed. 12 , 15 …”
Section: Methodsmentioning
confidence: 99%
“…In the research performed by Ju et al, the authors found that PLFCS and functional connection strength (FCs) were higher in the AD and MCI groups when compared to the normal control group. The study concludes that brain FC abnormality is correlated with tau pathology in AD and MCI [ 10 ].…”
mentioning
confidence: 99%